Environmental Managemen Model in Coastal Area (Case Study of Ekopesantren al-Khairat Palu Sulawesi Tengah) - Rihlah Nur Aulia; F M Jasin; Dewi Anggraeni; Sari Nurulita; Izzatul Mardhiah; Andy Hadiyanto (Nusantara Science and Technology Proceedings)
This study aims to determine the environmental management model in coastal areas based on ecosystems; Al-Khairat Islamic Boarding School in Central Sulawesi, Case Study. Optimizing environmental conservation is done through many factors, and religious elements become one of these factors; religion becomes a way to shape the character of its adherents in protecting their environment. Islam as a religion has teachings that direct its supporters to protect the environment adequately so that the instructions are in harmony with the concept of environmental conservation. This research uses ekopesantren theory with several indicators. First, the pesantren policy that carries out environmental management by utilizing the land to create artificial forests. Utilization is based on agroforestry, agro silvopasteur and agro fishery approach. The zone of mangrove forest utilization can help food security and environmental preservation in the boarding school environment. The existence of an artificial lake as a water catchment area supports efforts to conserve water in boarding schools. It also serves as a water reserve through rainwater collection so that it can minimize the occurrence of flooding. Second, participatory activity-based environmental development policies. Islamic boarding schools make santri as an aid team in overcoming natural disasters and ecological disasters to minimize environmental damage, social impacts, and economic losses. The environmental management model carried out by the Al-Khairat Islamic Boarding School in Palu in the coastal area and geographically crossed by the equator, can reduce environmental damage and can be used as a role model in disaster mitigation and eco-implementation implementation.